1998
DOI: 10.1159/000022778
|View full text |Cite
|
Sign up to set email alerts
|

Linkage of Autosomal Recessive Primary Congenital Glaucoma to the GLC3A Locus in Roms (Gypsies) from Slovakia

Abstract: The autosomal recessive form of primary congenital glaucoma (gene symbol GLC3) has been recently mapped to two different loci, GLC3A (at 2p21), and GLC3B (at 1p36), respectively, on families of Turkish and Saudi Arabian provenance. This disorder is known to occur with an extremely high incidence in Roms (Gypsies) in Slovakia. We performed a standard linkage analysis on a sample of 7 Slovak Gypsy families comprising 18 affected members, and found significant linkage with four STR markers from the chromosomal re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0
1

Year Published

1999
1999
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(17 citation statements)
references
References 8 publications
(17 reference statements)
1
15
0
1
Order By: Relevance
“…This percentage is much lower than the 90% to 100% found in Slovakian Romas, the 44% reported in Indian patients, and the 50% reported in Brazilian patients with primary congenital glaucoma. 2,9 This incident rate is comparable with the 15% to 20% rate reported in Japanese and Chinese primary congenital glaucoma populations. 10,32 In our cohort, the pathogenic CYP1B1 sequence variants comprised 3 missense amino acid changes, 2 nonsense amino acid changes, a 10-bp insertion, and a 13-bp deletion (Figure 3).…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…This percentage is much lower than the 90% to 100% found in Slovakian Romas, the 44% reported in Indian patients, and the 50% reported in Brazilian patients with primary congenital glaucoma. 2,9 This incident rate is comparable with the 15% to 20% rate reported in Japanese and Chinese primary congenital glaucoma populations. 10,32 In our cohort, the pathogenic CYP1B1 sequence variants comprised 3 missense amino acid changes, 2 nonsense amino acid changes, a 10-bp insertion, and a 13-bp deletion (Figure 3).…”
Section: Discussionsupporting
confidence: 59%
“…8 The proportion of patients with pathogenic CYP1B1 sequence variants varies with ethnicity, ranging from 100% in Slovakian Romas to 20% in Japanese individuals. 9,10 …”
mentioning
confidence: 99%
“…Mutations of these genes can cause IPCG [Stoilov et al, 1997[Stoilov et al, , 1998]. Plašilova et al [1998] demonstrated that IPCG in the Gypsy population of Slovakia is also due to the locus GLC3A and consequently to the mutations in the cytochrome P4501B1. Later Plašilova et al [1999] showed that within P4501B1 gene the E387K mutation is characteristic for Gypsies having originated from a single ancestral mutational event as a founder effect.…”
Section: Discussionmentioning
confidence: 99%
“…The high incidence of IPCG and IAM with-in general-autosomal recessive origin in Gypsy children may be connected with a high rate of consanguinity in Gypsy communities, 15,16 and a founder gene mutation in the Central European Gypsy population in the origin of IPCG. 17,18 In general the mothers of cases born with CAs belong to the social groups with lower SES 19 which is partly explained by confounders and etiological factors connected with the low SES and partly by the consequences of the birth of malformed babies with serious medical, familial and financial burden. The possible other etiological factors including life styles were presented and discussed in our previous papers.…”
Section: Discussionmentioning
confidence: 99%